Retratos da Manguetown: as imagens da cidade nas letras de Chico Science - Satorno, Marla Silva do Vale (2011)
The main purpose of this study is to analyze the urban images which are present in Chico Science’s lyrics. Science is the Pernambucan artist who is the most important representative of a musical and cultural move-ment named Mangue. The type of music which finds its origin in this movement is called Mangue-beat, referring to a sound that mixes punk, rap and rock and roll to traditional rhythms from the Brazilian Northeast, such as Maracatu. We also focus on aspects of the culture and identity of Northeastern Brazil, where many of the cultural features differ from the rest of the country. Besides this, we also show how contemporary poetry and music have been influenced by the first modernist poets, who found their inspiration in the city and its way of life. These modernist poets also influenced poetry in the second half of 19th Century and in the beginning of the 20th Century, and even today have a strong presence in the arts.We discuss a selection of Chico Science’s lyrics written between 1994 and 1996 using literary theories of modern poetry as well as theories from the area of Cultural Studies that deal with cultural and regional identity.